Eruption Style, Emplacement Dynamics and Geometry of Peralkaline Ignimbrites: Insights From the Lajes-Angra Ignimbrite Formation, Terceira Island, Azores - Pimentel, Adriano; Self, Stephen; Pacheco, José M.; Jeffery, Adam J.; Gertisser, Ralf (Frontiers in Earth Science, 2021)
Ignimbrites are relatively uncommon on ocean island volcanoes and yet they constitute a significant portion of the stratigraphy of Terceira Island (Azores). The Lajes-Angra Ignimbrite Formation (ca. 25 cal ka BP) contains the youngest ignimbrites on Terceira and records two ignimbrite-forming eruptions of Pico Alto volcano that occurred closely spaced in time. Here, we present the first detailed lithofacies analysis and architecture of the Angra and Lajes ignimbrites, complemented by petrographic, mineral chemical, whole rock and groundmass glass geochemical data. The two ignimbrites have the same comenditic trachyte composition but show considerable variability in trace element and groundmass glass compositions, revealing complex petrogenetic processes in the Pico Alto magma reservoir prior to eruption. The Angra Ignimbrite has a high aspect-ratio and is massive throughout its thickness. It was formed by a small-volume but sustained pyroclastic density current (PDC) fed by a short-lived, low pyroclastic fountain. Overall, the PDC had high particle concentration, granular fluid-based flow conditions and was mostly channelled into a valley on the south part of Terceira. By contrast, the Lajes Ignimbrite has a low aspect-ratio and shows vertical and lateral lithofacies variations. It was formed by a sustained quasi-steady PDC generated from vigorous and prolonged pyroclastic fountaining. The ignimbrite architecture reveals that depositional conditions of the parent PDC evolved as the eruption waxed. The dilute front of the current rapidly changed to a high particle concentration, granular fluid-based PDC that extended to the north and south coasts, with limited capacity to surmount topographic highs. Contrary to what is commonly assumed, the low-aspect ratio of the Lajes Ignimbrite is interpreted to result from deposition of a relatively low velocity PDC over a generally flat topography. This work highlights that the geometry (aspect ratio) of ignimbrites does not necessarily reflect the kinetic energy of PDCs and thus should not be used as a proxy for PDC emplacement dynamics. Although the probability of an ignimbrite-forming eruption on Terceira is relatively low, such a scenario should not be underestimated, as a future event would have devastating consequences for the island’s 55,000 inhabitants.